Development of a standardized histopathology scoring system for intervertebral disc degeneration in rat models: An initiative of the ORS spine section. Issue 2 (26th May 2021) - Lai, Alon; Gansau, Jennifer; Gullbrand, Sarah E.; Crowley, James; Cunha, Carla; Dudli, Stefan; Engiles, Julie B.; Fusellier, Marion; Goncalves, Raquel M.; Nakashima, Daisuke; Okewunmi, Jeffrey; Pelletier, Matthew; et al.
Abstract: Background: Rats are a widely accepted preclinical model for evaluating intervertebral disc (IVD) degeneration and regeneration. IVD morphology is commonly assessed using histology, which forms the foundation for quantifying the state of IVD degeneration. IVD degeneration severity is evaluated using different grading systems that focus on distinct degenerative features. A standard grading system would facilitate more accurate comparison across laboratories and more robust comparisons of different models and interventions. Aims: This study aimed to develop a histology grading system to quantify IVD degeneration for different rat models. Materials & Methods: This study involved a literature review, a survey of experts in the field, and a validation study using 25 slides that were scored by 15 graders from different international institutes to determine inter‐ and intra‐rater reliability. Results: A new IVD degeneration grading system was established and it consists of eight significant degenerative features, including nucleus pulposus (NP) shape, NP area, NP cell number, NP cell morphology, annulus fibrosus (AF) lamellar organization, AF tears/fissures/disruptions, NP‐AF border appearance, as well as endplate disruptions/microfractures and osteophyte/ossification. The validation study indicated this system was easily adopted, and able to discern different severities of degenerative changes from different rat IVD degeneration models with high reproducibility for both experienced and inexperienced graders. In addition, a widely‐accepted protocol for histological preparation of rat IVD samples based on the survey findings include paraffin embedding, sagittal orientation, section thickness < 10 μm, and staining using H&E and/or SO/FG to facilitate comparison across laboratories. Conclusion: The proposed histological preparation protocol and grading system provide a platform for more precise comparisons and more robust evaluation of rat IVD degeneration models and interventions across laboratories. Abstract : Standardized histopathology scoring system with different categories and features for quantifying intervertebral disc degeneration in rat models.